TEACHER DISCOURSE IN EFL CLASSROOM: A GENDER AND DISCOURSE STUDY - Laila Ulsi Qodriani; Zahra Muti’ah (Kantor Bahasa Lampung, 2017)
AbstractThe relationship between language and gender has long been interest within sociolinguistic andrelated disciplines. In particular, it looks at the ways in which male and female use languagedifferently. Thus, the objective of the present study is to find out and describe how male andfemale teachers in EFL classroom use language differently in the classroom interaction,particularly in English Speaking class. This exploratory case study was carried out with 2 male and2 female English Speaking 1 teachers of English Literature Study Program Universitas TeknokratIndonesia. The data collected included direct observation of classroom interaction, audio andvideo recording of the teacher and students` interactions. The analysis of the data revealed that infact both male and female teachers used language to advice the students. It was all because theaim of teaching is to improve students’ ability, so the teachers frequently used language to giveadvices and suggestions for the students’ improvement. In the other hand, male teachers morefocus on the goal of teaching to maintain their status meanwhile female teachers more concern onthe process of teaching to build relationship with the students. AbstrakHubungan antara bahasa dan gender telah lama diminati dalam sosiolinguistik dan disiplin terkait.Secara khusus, hal ini dapat melihat cara penggunaan bahasa oleh pria dan wanita secaraberbeda. Oleh sebab itu, tujuan dari penelitian ini adalah untuk mengetahui dan menggambarkanbagaimana guru pria dan wanita di kelas EFL menggunakan bahasa secara berbeda dalaminteraksi kelas, khususnya dalam kelas Berbahasa Inggris. Studi kasus eksplorasi ini dilakukan pada2 orang guru pria dan 2 orang guru wanita kelas bahasa Inggris 1 Program Studi Sastra InggrisUniversitas Teknokrat Indonesia. Data yang dikumpulkan meliputi pengamatan langsung terhadapinteraksi kelas, rekaman audio dan video interaksi guru dan siswa. Analisis data menunjukkanbahwa guru laki-laki dan perempuan menggunakan bahasa untuk memberi nasehat kepada siswa.Itu semua karena tujuan pengajarannya adalah untuk meningkatkan kemampuan siswa, sehinggapara guru sering menggunakan bahasa untuk memberi nasehat dan saran untuk peningkatansiswa. Di sisi lain, guru laki-laki lebih fokus pada tujuan mengajar untuk mempertahankanstatusnya sementara guru perempuan lebih memperhatikan proses pengajaran untukmembangun hubungan dengan siswa.